Aprendiendo Español Como Lengua Extranjera A Través Del Uso Didáctico De Películas Del Cine Colombiano (2022)
Much of the Colombian cultural richness that is reflected in the music, the cinema, or in real life situations, could be used to provide those who are learning the Spanish language, an approach to the way in which the people when they interact according to the environment or the context in which they are. Normally, when learning a language, it focuses more on clearly grammatical, leaving aside the cultural aspects that can favor the development of communicative competences, for his part Altamirano (2006), states that, "we must make the student see that the language is not referred to a grammar book where it is shown rules that are generally not related to their daily life” (p. 227). Therefore, when learning a language, it is considered necessary to take into account take into account cultural aspects, since it would help to understand the expressions or words belonging to a certain sociocultural context, which could generate confusion for a foreigner when he listens to them, because he must analyze and interpret its meaning or intent. Likewise, Spanish has multiple linguistic variants, which, depending on the region or country in which it is found, tend to to have different meanings. 6 On the other hand, if the learning of a language is focused on aspects sociocultural will require constant practice to achieve mastery or at least its knowledge, that is why it is considered important that whoever is learning it can show how is the interaction of individuals in a given context and if it is possible to interact with them, either in person or with the use of materials authentic uploaded on different virtual platforms, to give you the confidence necessary when using words or expressions that allow you to communicate in events real. Beltrán (2017) says that every situation that a foreign language student have to deal with native speakers, he will put into practice the language he is learning to solve different tasks communicate and complete their learning process. In addition, Colombia could attract the attention of foreigners, due to its wealth culture and diversity, which has caused different aspects to emerge that give a certain identity to each region, for example, dialects and different expressions that might be of interest to first-time visitors or those want to learn the Spanish that exists in the Colombian context, and enrich their vocabulary to wave in the Colombian culture and to be able to identify the characteristics that colloquial expressions have and the effect they have on people when they are they use. This allows us to analyze that the colloquial expressions used daily in Colombian contexts, could be useful for students to foreigners can know and identify them through the different tools technological technologies reflected in the cinema, television, radio, etc., allowing engage with the real context and show the purpose of the words that could be 7 unknown to them. Likewise, when teaching the linguistic variants typical of the Colombian context, could be achieved through the use of communication technologies communication, since currently connection networks allow users to foreign students, have access to the necessary information to acquire new vocabulary and identify expressions that are part of informal communication.